Coordination as a best practice from the polio eradication initiative: Experiences from five member states in the African region of the World Health Organization. Issue 43 (10th October 2016) - Okeibunor, Joseph; Nsubuga, Peter; Salla, Mbaye; Mihigo, Richard; Mkanda, Pascal
Highlights: Structures were put in place to ensure coordinated mobilization of resources for PEI. With the recorded successes, the structures became attractive to other public health interventions. The PEI structures were deployed to respond to other diseases interventions. This paper documents the structure for more systematic deployment for future public health interventions. Abstract: Background: As part of the efforts to eradicate polioviruses in the African Region, structures were put in place to ensure coordinated mobilization and deployment of resources within the framework of the global polio eradication initiative (PEI). The successes of these structures made them not only attractive to other public health interventions, but also caused them to be deployed to the response efforts of other diseases interventions, without any systematic documentation. This article documents the contributions of PEI coordination units to other public health interventions in the African Region of World Health Organization Methods: We reviewed the contributions of PEI coordination units to other public health interventions in five countries in the African Region. Results: The analysis identified significant involvement of PEI coordination structures in the implementation of routine immunization programs in all the countries analyzed. Similarly, maternal and child health programs were planned, implemented, monitored and evaluation the Inter-Agency Coordination Committees of the PEI programs in the different countries. The hubs system used in PEI in Chad facilitated the efficient coordination of resources for immunization and other public health interventions in Chad. Similarly, in the Democratic Republic of Congo PEI led coordination activities benefited other public health programs like disease control and the national nutrition program, the national malaria control program, and the tuberculosis control program. In Nigeria, the polio Expert Review Committee effectively deployed the Emergency Operation Center for the implementation of prioritized strategies and activities of the National Polio Eradication Emergency Plan, and it was utilized in the response to Ebola Virus Disease outbreak in the country. Conclusions: The PEI-led coordination systems are thus recognized as having made significant contribution to the coordination and delivery of other public health interventions in the African Region.